Psychomotor development of preterm infants aged 6 to 12 months - Eickmann, Sophie Helena; Malkes, Natália Ferraz de Araújo; Lima, Marília de Carvalho (São Paulo Medical Journal, 2012)
CONTEXT AND OBJECTIVE: The immaturity of preterm infants’ organ systems may lead to difficulties in adapting to different environmental stimuli. The aim was to compare the psychomotor development of preterm infants (with corrected age) and term infants aged 6 to 12 months and to investigate associated factors. DESIGN AND SETTING: Cross-sectional analytical study conducted at Hospital das Clínicas, Universidade Federal de Pernambuco. METHODS: The sample consisted of 135 infants (45 preterm and 90 full-term) aged 6 to 12 months. Neuropsychomotor development was assessed using the Bayley III cognitive, language and motor subscales. Biological, socioeconomic and demographic data were gathered from medical records and through interviews with mothers. RESULTS: The mean cognitive, language and motor indices were within the range of normality for the sample as a whole. No significant difference in the development of infants born preterm and full-term was observed, except for expressive communication, in which preterm infants presented a lower index. Motor development was influenced by biological factors, and the poorest performances were observed in male infants; birth weight birth weight < 1500 g; Apgar score at five minutes ≤ 7; weight-, length- and head circumference-for-age < -1 Z-score; and exclusively breastfeeding for ≤ two months. CONCLUSIONS: Prematurity did not influence the psychomotor development of infants in this study population. Motor development was the most affected domain in the sample as a whole, especially due to biological factors. Investigations on child neuropsychomotor development should try to identify many determinant factors because of its multifactorial nature.